How Moon Fuentez fell in love with the universe - Vasquez Gilliland, Raquel (Simon & Schuster BFYR, 2021)
When seventeen-year-old Star Fuentez reaches social media stardom, her polar-opposite twin, Moon, becomes "merch girl" on a tour bus full of beautiful influencers and the grumpy but attractive Santiago Philips.